Metody Asymptotyczne w Teorii Tarczy z Mikrostrukturą - K. Wilmański (Engineering Transactions, 1967)
This paper is devoted to the application of asymptotic methods to the set of equations describing a plane body with microstructure. The property of this body consisting in the presence of a small parameter at the differential operators of the highest order is made use of. The solution is. represented in the form of a sum of functions from two iteration processes. The procedure is based on the works of Goldenweiser in which the present method is applied in the theory of shells. The paper ends by an example in which the method is applied to a fibrous medium, which is a continuous model of a polar grate.